Intelligent elderly care II - Weong, Yen Teng (2014)
With the number of cases of dementia set to increase in numbers in the coming years, with Singapore's greying population on the rise and the number of young citizens to support and look after the an elderly decreasing. The industry for silver care is in the market as developers are looking into ways to incorporate technology into elderly care to improve and assist caregivers in looking after the needs of the elderly.